Neutrophil to lymphocyte ratio predicts poor functional capacity in patients with heart failure - Musa Çakıcı; Mustafa Çetin; Adnan Dogan; Muhammed Oylumlu; Erdal Aktürk; Mustafa Polat; Arif Suner; Sabri Abuş (KARE Publishing, 2014)
Objectives: We aimed to assess the relationship between neutrophil to lymphocyte ratio (N/L ratio) and functional capacity (FC) of patients with compensated heart failure (CHF). Study design: A total of 94 consecutive CHF patients and age-gender matched 70 subjects with normal echocardiographic examination were enrolled. Peripheral venous blood samples were drawn before echocardiography examination and treadmill test in all study population. The treadmill test based on modified Bruce protocol was used to determine the functional status of CHF patients. Poor FC was defined as <5 metabolic equivalant (MET) in the exercise test. Afterwards, patients with CHF were divided into two groups with respect to the top and bottom 3 of the N/L ratio. Results: FC (3.2+-2.05 MET vs. 6.1+-2.04 MET, p<0.001), ejection fraction (%31.5+-7.64 vs. %34.8+-6.82, p=0.028) were found to be lower and N-terminal pro-brain natriuretic peptide (NT-proBNP) level (3360+-2742 pg/dl vs. 1613+-1334 pg/dl, p<0.001) pulmonary artery pressure (46.3+-11.50 mmHg vs. 41.5+-9.45 mmHg, p=0.049), left atrial diameters (4.6+-0.52 cm vs. 4.3+-0.43 cm, p=0.005), E/Ea ratio (12.2+-4.37 vs. 9.2+-3.20, p<0.001) were found to be higher in CHF patients with an N/L ratio >3 than with an N/L ratio <3. The N/L ratio, and log- NT-proBNP level were determined to be a predictive factor of poor FC (odds ratio [OR]=3.085, 95% confidence interval [CI] = 1.520-6.260, p=0.002 and OR=1.585, 95% CI=1.201-2.091, p=0.001, respectively). A cut-off point of 2.74 for the N/L ratio had 79.4% sensitivity and 80% specificity in predicting poor FC. Conclusion: N/L ratio can be used to predict poor FC in patients with CHF.